The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.joc.2c00014
|View full text |Cite
|
Sign up to set email alerts
|

Sarglaromatics A–E: A Class of Naphthalene-Like Architecture Fused Norlindenane Sesquiterpene Dimers from Sarcandra glabra

Abstract: Sarglaromatics A−E (1−5, respectively), five unprecedented naphthalene-like architecture-fused norlindenane sesquiterpene dimers, were discovered from the roots of Sarcandra glabra. The unique naphthalene core skeleton was obtained from classical lindenane [4 + 2] dimers via a free-radical-mediated C11− C11′ bond formation reaction and 12'-decarboxylation. The highly fused octonary ring skeleton was elucidated by HRMS, NMR, ECD, quantum chemical calculations, and biogenetic inspiration. Compounds 1 and 2 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…and carbonyl (1755 and 1701 cm −1 ) groups. The 1 H NMR spectrum (Table 1) showed a pair of high-field methylene signals of the 1,2-substituted cyclopropane ring, indicating the presence of a lindenane-type sesquiterpenoid in 1, [9][10][11] which was further identified by the cross peaks of H-1 (δ H 1.94, m)/H-2 (δ H 0.79, m, 0.65, m)/H-3 (δ H 2.01, m) in the 1 H-1 H COSY spectrum. In the 13 C NMR spectrum, only 10 carbons remained to be Jiangsu Key Laboratory of Bioactive Natural Product Research, State Key Laboratory of Natural Medicines, Department of Natural Medicinal Chemistry, China Pharmaceutical University, 24 Tong Jia Xiang, Nanjing 210009, People's Republic of China.…”
Section: Introductionmentioning
confidence: 99%
“…and carbonyl (1755 and 1701 cm −1 ) groups. The 1 H NMR spectrum (Table 1) showed a pair of high-field methylene signals of the 1,2-substituted cyclopropane ring, indicating the presence of a lindenane-type sesquiterpenoid in 1, [9][10][11] which was further identified by the cross peaks of H-1 (δ H 1.94, m)/H-2 (δ H 0.79, m, 0.65, m)/H-3 (δ H 2.01, m) in the 1 H-1 H COSY spectrum. In the 13 C NMR spectrum, only 10 carbons remained to be Jiangsu Key Laboratory of Bioactive Natural Product Research, State Key Laboratory of Natural Medicines, Department of Natural Medicinal Chemistry, China Pharmaceutical University, 24 Tong Jia Xiang, Nanjing 210009, People's Republic of China.…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional Chinese medicinal material, the xylem of S. glabra can clear away heat and detoxification, dispel wind and activate blood circulation, reduce swelling and pain, and resist bacteria and inflammation. In recent years, many studies had shown that S. glabra has acetylcholinesterase (AchE) inhibitory activity, [4] anti-inflammatory, [5] anti-tumor, anti-bacterial, [6] antifungal activities, [7,8] and inhibitory activity of lipid accumulation. Previous phytochemistry researches of this plant revealed the presence of coumarins, sesquiterpenes, and neolignans.…”
Section: Introductionmentioning
confidence: 99%
“…The unchanged degree of unsaturation and disappearance of Δ Subsequently, the X-ray diffraction (XRD) experiment on the crystal of 2 under Cu Kα radiation was successful, and the XRD data (CCDC 2158552, MeOH/H 2 O) confirmed its planar structure and absolute configuration as 1R,3S,5S,7S,8R,9S,10S,11R,4′S,5′R [Figure 4; Flack parameter = 0.04 (10)]. To validate the structural relationship of 1/3 and 2, the electronic circular dichroism (ECD) calculations of 1−3 at the B3LYP/6-311+G(2d,p) level with the PCM in methanol were conducted.…”
mentioning
confidence: 99%